Extraction and characterization of Jatropha Curcas Linnaues seed oil through soxhlet method - Mani, Shalini (2013)
Decrease in fossil fuel production due to depletion of petroleum resources and concern toward environmental have made the world to turn into renewable energy, biofuel and reduce its dependency on fossil fuel.Jatropha oil,less expensive feedstock as it is inedible oil has been used as biofuel raw material instead of edible oils which are more expensive because of its competitive food uses.This study was carried out to investigate the performance of soxhlet extraction in the extraction of jatropha oil from Jatropha curcas Linnaeus seed under three main factors which were extraction solvent, ethyl acetate and ethanol,extraction time,6 hour,8 hour and 10 hour and solvent to solid ratio, 7.5:1, 10:1 and 12.5:1.Current extraction solvent used for jatropha oil extraction in industry is n-hexane which is listed as hazardous air pollutant (HAP).Hence,an alternative solvent which is more environmental-friendly and yields comparable result with n-hexane are studied.The best extraction condition that has been determined for maximum jatropha oil production was under solvent ethyl acetate at 8 hour extraction time and highest solvent to solid ratio. This optimum condition was finalized based on its maximum yield of jatropha oil which was 47.38% (w/w).Then, the oil samples at different extraction time were analyzed to evaluate its quality by determining its chemical constituent through GC-MS.The main components detected in the jatropha oil with solvent ethyl acetate and 8 hour extraction time were oleic acid, linoleic acid, palmitic acid, stearic acid, oleoaldehyde,methyl linolate,ethyl oleate,methyl linolelaidate,methyl stearate and squalene where oleic acid and linoleic acid are the dominant component for most of the oil recovered through extraction.Soxhlet extraction method is much more efficient than other extraction method in term of cost,operability and also yield of oil,quantitatively and qualitatively.Besides,ethyl acetate has been chosen as suitable alternative environmentally friendly as it gives comparable result with n-hexane.